Paraquat intoxication and hemocarboperfusion. - Castro, Rui (2005)
In the northeast of Portugal, paraquat intoxication is common. We report 31 patients, admitted at our institution from April 1997 to June 2004, with suspected paraquat intoxication. Thirty cases had suicidal intention and all have ingested the toxic by mouth. Treatment consisted of skin and digestive decontamination with gastric washing and activated charcoal or Fuller's Earth. The first medical care was performed after 1 h 14 min at median [9 min-11 h 26 min]. By laboratory measurement (n=13) and/or clinical observation (n=11) it was possible to confirm the gastrointestinal absorption of paraquat for 24 patients (17 male-7 female; 49 +/- 17 years). The estimated ingested volume was higher for 15 non-survivors relatively to nine survivors (170 +/- 60 mL vs 25 +/- 10 mL; P